COMPARATIVE EVALUATION OF BLOOD CULTURE AND C-REACTIVE PROTEIN (CRP) DETECTION IN THE DIAGNOSIS OF NEONATAL SEPSIS" - SNEHA S HEGADI; KALPANA S (International Journal of Pharma and Bio Sciences, 2015)
Neonatal septicemia is the commonest cause of neonatal mortality and morbidity.Prompt diagnosis of neonatal sepsis is usually difficult often due to nonspecific clinical symptoms and bacterial cultures are time-consuming. In this study, we have made a comparative evaluation of blood cultures and CRP detection in early diagnosis of neonatal sepsis.A total of 200 clinically suspected neonatal septicemic cases were subjected to aerobic culture and rapid diagnostic tests like C-reactive protein (CRP) detection by qualitative rapid latex slide tests.Among the 46% blood culture positive cases, CRP >6 mg/dl were seen in 90.21% and among the blood culture negative seen in 9.78%.Blood culture remains the gold standard for the diagnosis of neonatal septicemia prior to antibiotic therapy in all clinically suspected septicemic cases but non cultural methods CRP estimation will help to initiate a presumptive treatment while awaiting for culture reports.